Modelling the geometry of the repeat unit cell of three-dimensional weave architectures - Buchanan, S.; Grigorash, A.; Quinn, J. P.; McIlhagger, A. T.; Young, C. (Journal of the Textile Institute, 2010)
The three-dimensional (3D) weaving process offers the ability to tailor the mechanical properties via design of the weave architecture. One repeat of the 3D woven fabric is represented by the unit cell. The model accepts basic weaver and material manufacturer data as inputs in order to calculate the geometric characteristics of the 3D woven unit cell. The specific weave architecture manufactured and subsequently modelled had an angle interlock type binding configuration. The modelled result was shown to have a close approximation compared to the experimentally measured values and highlighted the importance of the representation of the binder tow path.